Genome sequencing provides new insights into metabolic versatility of lysinibacillus sphaericus : a novel approach in effective degradation of aromatic hydrocarbons (2016)
Microorganisms play a key role in carbon recycling around the world. Because of their enormous functional diversity, they can even degrade organic compounds that most animals and p ants cannot, as aromatic hydrocarbons. Thus, microorganism can be used in bioremediation strategies for mitigating the adverse health effects of petroleum compounds. In this study, we sequenced the genome of L. sphaericus 2362 and found genes involved in aromatics degradation. We evaluated the biodegradation of mono- and poly-aromatics hydrocarbons by providing toluene, naphthalene, and phenanthrene as a sole carbon source